Evidence that Neurons Harbor Latent Herpes Simplex Virus - Cook, M. L. (1974)
The cell type(s) harboring latent herpes simplex virus in the spinal ganglia of mice was investigated. Taken together, results from immunofluorescence, electron microscopic, autoradiographic, and in situ nucleic acid hybridization methods suggest strongly that, in mice, latent virus is maintained in neurons.